Biopolymeric coatings for delivery of antibiotic and controlled degradation of bioresorbable Mg AZ31 alloys. Issue 11 (24th July 2017) - Zomorodian, A.; Ribeiro, I. A.; Fernandes, J. C. S.; Matos, A. C.; Santos, C.; Bettencourt, A. F.; Montemor, M. F.
ABSTRACT: Magnesium and magnesium alloys are attracting considerable interest as biodegradable materials with high potential for application as temporary implants. The high corrosion rate of Mg-based implants is considered a serious drawback, and it is crucial to design novel surface protection strategies that minimize the detrimental effects of corrosion, while contributing for introducing additional functionalities on the material surface. In this work, a layer-by-layer coating architecture composed of an inner poly(lactic- co -glycolic) acid layer, working as adhesion promoter, and additional polycaprolactone (PCL) layers working as reservoirs for antibiotic (levofloxacin) and for nanohydroxyapatite (nanoHA) particles was applied on the Mg alloy AZ31. The results demonstrate that the composition and number of PCL layers can tailor the biodegradation of the bare magnesium alloy, surface wettability, and the kinetics of release of antibiotic (levofloxacin). The distribution of nanoHA in the coating architecture plays a crucial role on tailoring the desired biocompatible functionalities and corrosion protection of the bare alloy. GRAPHICAL ABSTRACT: